Evaluation of the efficacy of green tea catechins as an adjunct to scaling and root planing in the management of chronic periodontitis using PCR analysis: A clinical and microbiological study - Hattarki, Sanjeevini A. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Increased knowledge of anaerobic bacteria in the development of periodontal diseases has led to new treatment strategies aiming primarily at suppression or elimination of specific periodontal pathogens. Over the last few decades, green tea has been subjected to many scientific and medical studies. AIM: The purpose of the present study was to assess the effect of green tea catechins on the red complex organisms using Polymerase Chain Reaction for microbiological analysis. MATERIALS AND METHODS: A split mouth study was conducted, in which a total of 20 subjects were included. Green tea catechin as local drug delivery was placed at study sites. Clinical parameters namely probing pocket depth (PPD), gingival index (GI), plaque index (PI) were recorded. Sub-gingival plaque samples were collected, and red complex micro-organisms were studied using PCR. Clinical and microbiological parameters were recorded at baseline, 1(st), and 5(th) week after treatment. RESULTS: The results showed statistically significant difference in PPD, GI, and PI and significant reduction of red complex organisms from baseline to 1(st) week and baseline to 5(th) week in both study and control groups (P < 0.001). Intergroup comparison between study and control group was statistically insignificant for PPD, PI, and GI. A significantly greater reduction in Tannerella forsythus (Tf) at 1(st) week and 5(th) week and Porphyromonas gingivalis (Pg) at 1(st) week was observed in study group when compared to control group. CONCLUSION: Green tea catechin can be used as an effective local drug delivery along with scaling and root planing in treatment of chronic periodontitis.